Hyper sexual, hyper masculine? : gender, race and sexuality in the identities of contemporary Black men - Slatton, Brittany C.; Spates, Kamesha (Ashgate, 2014)
"This book provides critical insights into the many, often overlooked, challenges and societal issues that face contemporary black men, focusing in particular on the ways in which governing societal expectations result in internal and external constraints on black male identity formation, sexuality and black 'masculine' expression. Presenting new interview and auto-ethnographic data, and drawing on an array of theoretical approaches methodologies, Hyper Sexual, Hyper Masculine? explores the formation of gendered and sexual identity in the lives of black men, shedding light on the manner in which these are affected by class and social structure. It examines the intersecting oppressions of race, gender and class, while acknowledging and discussing the extent to which black men's social lives differ as a result of their varying degrees of cumulative disadvantage. A wide-ranging and empirically grounded exploration of the intersecting roles of race, masculinity, and sexuality on the lives of black men, this volume will appeal to scholars across the social sciences with interests in race and ethnicity, gender and sexuality, social stratification and intersectionality"--Provided by publisher